The extraction of papain enzymes from papaya leaves - Masita, Md Isa (2010)
Due to importance of maximizing commercial value of papaya fruits, selection of papaya leaves as raw material in extracting papain enzymes is necessary to maintain the sales value of the fruit. The aim of the present study is to find out the best pre-treatment approach in extracting papain enzymes from papaya leaves as well as to determine the optimum parameter for the extraction process. The leaves were subjected to a pre-treatment approach followed by hot water extraction process and then, enzymatic analysis. Among various pre-treatment approaches, maximum amino acids concentration, 0.15 mol/liter was achieved when grinding incorporated with ultrasonication was applied. The optimum period for extraction was 4 hours while optimum temperature was at 65°C. At this optimum condition, 0.45 mol/liter amino acids was achieved after grinding incorporated with ultrasonication sample undergo extraction process while 0.41 mol/liter amino acids was achieved after enzyme treatment incorporated with ultrasonication sample undergo extraction process. Utilization of HPLC is highly recommended to get the actual yield of papain enzymes being extracted without being declared as other substances.